2018
DOI: 10.1186/s12882-017-0805-1
|View full text |Cite
|
Sign up to set email alerts
|

Uncontrolled donation after circulatory death: comparison of two kidney preservation protocols on graft outcomes

Abstract: BackgroundKidney transplantation following uncontrolled donation after circulatory death (uDCD) presents a high risk of delayed graft function due to prolonged warm ischemia time. In order to minimise the effects of ischemia/reperfusion injury during warm ischemia, normothermic recirculation recently replaced in situ perfusion prior to implantation in several institutions. The aim of this study was to compare these preservation methods on kidney graft outcomes.MethodsThe primary endpoint was the one-year measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 38 publications
0
29
0
1
Order By: Relevance
“…Recent literature on the topic reveals that nRP can substantially reduce the incidence of PNF among uDCD kidney transplants, compared with the in situ cooling of kidneys . The function of uDCD kidneys subject to nRP is also better . In fact, large series of uDCD kidneys show extraordinary outcomes with this approach .…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature on the topic reveals that nRP can substantially reduce the incidence of PNF among uDCD kidney transplants, compared with the in situ cooling of kidneys . The function of uDCD kidneys subject to nRP is also better . In fact, large series of uDCD kidneys show extraordinary outcomes with this approach .…”
Section: Discussionmentioning
confidence: 99%
“…Less is known about the effects of NRP on renal transplant outcomes. However, a large recent nonrandomized study showed that there was no statistically significant difference in the rates of delayed graft function in kidneys preserved by cold storage compared with the use of NRP …”
Section: Discussionmentioning
confidence: 99%
“…van de Leemkolk et al abdominal organs included in the studies concerned: kidney (n = 9), 24,[26][27][28]34,36,37,41,45 liver (n = 11), 21,25,29,31,32,39,40,[42][43][44]46 kidney and liver (n = 1), 30 and kidney, liver, and pancreas/islets (n = 3). 33,35,38 The overlap in partly duplicate reporting on the same organ is outlined in Table 2.…”
Section: Study Characteristicsmentioning
confidence: 99%